Strategic Planning of Palestinian Higher Education and Its Relationship to National Strategic Planning in Light of Some Sustainable Development Indicators - Masharqa, Odetallah (Jordan Journal of Business Administration, 2021)
The ultimate purpose of this research is to shed light on the relationship between the national strategic planning of Palestine and the strategic planning of the Palestinian higher-education system, as well as the extent of compatibility and integration between them. This will lead to achieving some indicators of sustainable development in Palestine. The research also investigated the ability of the State of Palestine to contribute to achieving the global commitments for sustainable development. Therefore, the method of content analysis was utilized in this research by reviewing the strategic planning data for the Palestinian Higher Education Ministry and the national strategic planning of other state ministries, as well as the data on sustainable development issued by the Palestinian Central Bureau of Statistics and Environmental Quality Authority. The study concluded that the Israeli occupation is a serious impediment to Palestine to achieve sustainable development, in addition to the absence of the foundations of complementarity and inclusiveness between the strategic planning of the Palestinian higher education and the general national strategic planning, the absence of the effective role of the Palestinian Higher Education Council in the national strategic planning of education and the lack of coordination and integration required among Palestinian universities. Accordingly, the study revealed weaknesses in the national strategic planning capacity to address sustainable development issues, especially in the indicators addressed by the research; namely, indicators of poverty, health care, higher education, security and peace, all within the social dimension, as well as unemployment, GDP, production and consumption patterns within the economic dimension and finally environmental dimension indicators; namely, water, wastewater and sewerage systems, marine and coastal environment, agriculture and land and biodiversity. Therefore, the researcher recommended the need to review the coordination between the strategic planning of the Palestinian higher education and the general national strategic planning, so as to ensure coordination, integration and inclusiveness in an attempt to achieve the goals of sustainable development 2030